Safety and Immunogenicity of Concomitant Administration and Combined Administration of Bivalent BNT162b2 COVID-19 Vaccine and Bivalent RSVpreF Respiratory Syncytial Virus Vaccine with or Without Quadrivalent Influenza Vaccine in Adults ≥ 65 Years of Age - Joel M. Neutel; Rahsan Erdem; Qin Jiang; Kevin Cannon; Helen Stacey; Ryan Newton; Emily Gomme; Wen Li; Federico J. Mensa; Özlem Türeci; Uğur Şahin; Kena A. Swanson; et al. (Vaccines)
Concomitant administration may improve vaccination rates. This analysis of a phase 1/2 randomized study included 1073 healthy ≥65-year-olds who previously received ≥3 mRNA COVID-19 vaccine doses. Participants received concomitantly administered RSVpreF and bivalent BA.4/BA.5-adapted BNT162b2 vaccine (concomitant administration) with or without quadrivalent influenza vaccine (QIV), admixed combined RSVpreF + BNT162b2 vaccine (combined vaccine) with or without QIV, RSVpreF, BNT162b2, or QIV. Immunogenicity objectives included demonstrating the noninferiority of neutralizing antibody titers elicited by concomitant administration and combined vaccine compared with RSVpreF or BNT162b2 administered alone, and by concomitant administration and combined vaccine given with QIV compared with RSVpreF, BNT162b2, and QIV alone. Reactogenicity (≤7 days) and safety ≤1 month (adverse events (AEs)) and ≤6 months (serious AEs (SAEs)) after vaccination were assessed. Noninferiority for all immunogenicity comparisons was demonstrated. All vaccine groups were well tolerated; no new safety concerns were identified. Reactogenicity was mostly mild/moderate with rates generally similar across groups, except injection site pain and fatigue, which were less frequent with RSVpreF + placebo vs. other groups. AEs were infrequent, mostly mild/moderate, occurring at similar frequencies across groups. No AEs leading to study withdrawal or vaccine-related SAEs were reported. Favorable safety and tolerability alongside similar immunogenicity provide support for concomitant or combined use of RSVpreF and BNT162b2, with or without QIV, to help protect older adults from these important respiratory pathogens (NCT05886777).